Faktor Yang Mempengaruhi Stock Price Volatility Perusahaan Pertambangan Di BEI (2015 – 2019) (Jurnal Paradigma Akuntansi, 2022)
This research aims to knowing the existence of dividend yield, dividend payout ratio, long term debt and earning volatility towards stock price volatility in mining companies listed on Indonesia Stock Exchange in 2015-2019. Samples selected by purposive sampling method and there are 9 companies of valid data. Data processing method using mutiple regression analysis through SPSS Program version 24 and Microsoft Excel 2013. The result of this reasearch shows that dividend yield gives positive significant influence towards stock price volatility, while dividend payout ratio, long term debt and earnings volatility have no influence towards stock price volatility. The aims of this research are to giving explaination and finding factors that affect stock price movements so it gives good signal to investors regarding factors that are important to consider in making investment decisions.